Hunting Zero (An Agent Zero Spy Thriller-Book #3) - Jack, Mars (Lukeman Literary, 2019)
"You will not sleep until you are finished with AGENT ZERO. A superb job creating a set of characters who are fully developed and very much enjoyable. The description of the action scenes transport us into a reality that is almost like sitting in a movie theater with surround sound and 3D (it would make an incredible Hollywood movie). I can hardly wait for the sequel." --Roberto Mattos, Books and Movie Reviews In HUNTING ZERO (Book #3), when CIA operative Agent Zero finds out his two teenage girls have been kidnapped and are bound for a trafficking ring in Eastern Europe, he embarks on a high-octane chase across Europe, leaving a trail of devastation is his wake as he breaks all rules, risks his own life, and does everything he can to get his daughters back. Kent, ordered by the CIA to stand down, refuses. Without the backing of the agency, with moles and assassins on all sides, with a lover he can barely trust, and being targeted himself, Agent Zero must fight multiple foes to get his girls back. Up against the most deadly trafficking ring in Europe, with political connections reaching all the way to the top, it is an unlikely battle-one man against an army-and one that only Agent Zero can wage. And yet, his own identity, he realizes, may be the most perilous secret of all. HUNTING ZERO (Book #3) is an un-putdownable espionage thriller that will keep you turning pages late into the night. "Thriller writing at its best." --Midwest Book Review (re Any Means Necessary) "One of the best thrillers I have read this year." --Books and Movie Reviews (re Any Means Necessary) Also available is Jack Mars' #1 bestselling LUKE STONE THRILLER series (7 books), which begins with Any Means Necessary (Book #1), a free download with over 800 five star reviews!
Keywords: Dobrodružství, napětí, thrillery